EFFECT OF DIFFERENT NITROGEN LEVELS AND ROW SPACING ON THE PERFORMANCE OF NEWLY EVOLVED MEDIUM GRAIN RICE VARIETY, KSK-133 - T. H. Awan; R. I. Ali; Z. Manzoor; M. Ahmad; M. Akhtar (Journal of Animal and Plant Sciences, 2011)
An experiment was carried out to study the effect of different Nitrogen levels (110,133 & 156 kg ha-1) in combination with different row spacing (15 cm, 22.5 cm & 30 cm). The experiment was conducted at Rice Research Institute Kala Shah Kaku during the crop growing season 2006 & 2007.Treatment RS2N3,where 156 Kg Nha-1 were applied with 22.5 cm row to row and plant to plant spacing had maximum values of plant height (79.07 cm), tillers m-2 (594), panicle length(25.40cm), No of grains panicle-1 (132.97), grain yield (5461.03 Kg ha-1), straw yield (9662.03 Kg ha-1) and least value of sterility %age (5.7 %). All these parameters were statistically at par with the treatment RS1N3 (15cm spacing with 156 Kg N ha-1) except panicle length. Statistically minimum values of all these parameters were recorded under the treatments RS1N1 (15cm spacing with 110 Kg N ha-1) and RS3N1 (30 cm spacing with 110 Kg N ha-1) except panicle length, 1000 grain weight & sterility %age. Harvesting index had non significant difference among all treatments
Keywords: Oryza sativa; row spacing; Nitrogen levels; yield components; paddy yield.